Dampak Perubahan Garis Pantai Terhadap Pemanfaatan Lahan Pesisir Kecamatan Tamalanrea Kota Makassar - Taufiqur Rachman; Hasdinar Umar; Ichwanul Haq Bahtiar (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2022)
area of ​​Makassar City is one of the areas experiencing significant land use changes. In addition, the pattern of changes in coastline from year to year that occurs in the coastal area of ​​Makassar City always experiences additions and decreases in coastal areas. This is due to the phenomena of accretion and abrasion and the sedimentation rate of the Tallo River formed in this area is quite large and continues to increase. The area directly affected and studied is Tamalanrea                      Sub-District. This study aims to analyze shoreline changes and their impact on land use over a period of 20 years in Tamalanrea Sub-District, using Landsat satellite imagery data. This research is expected to provide benefits to local governments as a basis for consideration in determining regional spatial planning policies, especially in the use of coastal land. The research method includes field observations, processing of oceanographic supporting data, digitizing and overlaying image data. Changes in the coastline for a period of 20 years (1998-2018) in Tamalanrea Sub-District were 20.14 Ha where the coastline that experienced accretion and abrasion was 12.20 Ha and 7.95 Ha, respectively. Changes in land use on the coast of Tamalanrea Sub-District for 18 years (2000-2018) which increased were residential land by 2.34 Ha, industrial/warehousing land by 82.37 Ha, public facilities land by 13.36 Ha, and mangrove land of 3.27 Ha. While the reduced land use is 70.89 Ha of wet land and 20.36 Ha of dry land. Changes in coastline to changes in land use in coastal areas in Tamalanrea Sub-District have physical, ecological/environmental, socio-economic, and institutional/legal impacts that are positive for the sustainable management of the coastal area of ​​Tamalanrea Sub-District.  It